Synthesis of chimeric tetrapeptide-linked cholic acid derivatives: impending synergistic agents - Bavikar, Sudhir N.; Salunke, Deepak B.; Hazra, Braja G.; Pore, Vandana S.; Dodd, Robert H.; Thierry, Josiane; Shirazi, Fazal; Deshpande, Mukund V.; Kadreppa, Sreenath; Chattopadhyay, Samit (Bioorganic & Medicinal Chemistry Letters, 2008)
Tetrapeptides derived from glycine and beta-alanine were hooked at the C-3 beta position of the modified cholic acid to realize novel linear tetrapeptide-linked cholic acid derivatives. All the synthesized compounds were tested against a wide variety of microorganisms (Gram-negative bacteria, Gram-positive bacteria and fungi) and their cytotoxicity was evaluated against human embryonic kidney (HEK293) and human mammary adenocarcinoma (MCF-7) cell lines. While relatively inactive by themselves, these compounds interact synergistically with antibiotics such as fluconazole and erythromycin to inhibit growth of fungi and bacteria, respectively, at 1-24 mu g/mL. The synergistic effect shown by our novel compounds is due to their inherent amphiphilicity. The fractional inhibitory concentrations reported are comparable to those reported for Polymyxin B derivatives. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Antimicrobial activity; Cholic acid; Cytotoxicity; Synergism; Tetrapeptide

Stereoselective synthesis and antimicrobial activity of steroidal C-20 tertiary alcohols with thiazole/pyridine side chain - Shingate, Bapurao B.; Liazra, Braja G.; Salunke, Deepak B.; Pore, Vandana S.; Shirazi, Fazal; Deshpande, Mukund V. (European Journal of Medicinal Chemistry, 2011)
Stereoselective synthesis of novel steroidal C-20 tertiary alcohols with thiazole and pyridine side chain using Grignard reaction of steroidal ketones and thiazole/pyridine magnesium bromide have been realized. These molecules were evaluated in vitro for their antifungal and antibacterial activities. Most of the compounds exhibited significant antifungal and antibacterial activity against all the tested strains. (C) 2011 Elsevier Masson SAS. All rights reserved.
Keywords: antibacterial activity; Antifungal activity; Grignard reaction; Steroid side chain; Steroidal ketones

Synthesis and antimicrobial activity of novel oxysterols from lanosterol - Shingate, Bapurao B.; Hazra, Braja G.; Salunke, Deepak B.; Pore, Vandana S.; Shirazi, Fazal; Deshpande, Mukund V. (Tetrahedron, 2013)
Chemically diverse oxysterols and their synthetic manipulations were carried out from variety of Delta(8(9)_) lanosterol derivatives and evaluated for their in vitro antimicrobial activities. Most of the synthesized oxysterols exhibited significant antifungal activity against the tested strains. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Allylic oxidation; antibacterial activity; Antifungal activity; Dihydroxylation; Oxygenated steroids